The Impact of Offshore Wind Farms on Increasing Electricity Production and Reducing CO2 Emissions - Malecha, Ziemowit; Chorowski, Maciej; Niechciał, Jakub (Instal, 2025)
This paper analyzes the actual impact of offshore wind farms on changes in the global capacity factor for wind energy. It also examines the real influence of unstable renewable energy sources (URES), namely photovoltaic and wind installations, on the reduction of CO2 emissions. The study utilizes available data from the years 2000–2023 for Denmark, Germany, and Poland — countries characterized by significantly different shares of URES in their energy mixes. The analysis demonstrates that the reduction of CO2 emissions is primarily correlated with a decrease in total electricity production. The effect of increasing installed URES capacity on emission reduction is secondary. It was also shown that the growing share of offshore wind farms in the wind energy sector does not translate into an increase in the global capacity factor (GCF). This may be related to lower-than-expected electricity generation from URES, as well as the necessity to curtail unstable sources due to the lack of demand (or technical ability) to accommodate additional electricity volumes within the grid.
Keywords: Unstable Renewable Energy Sources; Offshore Wind Farms; Global Capacity Factor; CO2 Emission Reduction